Aging With HIV: Health Policy and Advocacy Priorities. (February 2021) - Brennan-Ing, Mark; Ramirez-Valles, Jesus; Tax, Aaron
The aging of people with HIV (PWH) is a major public health accomplishment and a social and cultural phenomenon. It highlights the human capacity to overcome adversity, the effectiveness of public health strategies (e.g., prevention and treatment), and the new challenges as well. Our societies are not well prepared to address the needs of older PWH and the changes they are creating. Stigma toward HIV, older age, and homosexuality, along with racism, have kept PWH largely invisible, resulting in limited investment in prevention and medical and social services. It is imperative that we develop an effective policy response to address the unique needs of PWH. The purpose of this article is to highlight current knowledge and emerging issues in HIV and aging to serve as a foundation on which to develop policy and program recommendations that will meet the new challenge.